Identification and characterization of opportunistic pathogen Pectobacterium polonicum causing potato blackleg in China - Han, Wanxin; Wang, Jinhui; Pirhonen, Minna; Pan, Yang; Qin, Jingxin; Zhang, Shangqing; Zhu, Jiehua; Yang, Zhihui (Frontiers in Plant Science, 2023)
Blackleg and aerial stem rot of potato (Solanum tuberosum L.), caused by soft rot enterobacteria of the genera Pectobacterium and Dickeya, has recently increased years in Hebei Province, China. Field surveys were performed during the 2021 potato growing season in Hebei to identify and characterize bacterial pathogens. Sixteen potato plants showing blackleg or aerial stem rot were collected from three potato-producing areas, and ten representative pectinolytic bacteria were isolated from symptomatic plants. 16S rDNA sequencing and multilocus sequence analysis were performed to determine the taxonomic position of the bacterial isolates. The isolates belonged to the genus Pectobacterium, including Pectobacterium atrosepticum, Pectobacterium carotovorum, Pectobacterium brasiliense, and Pectobacterium parmentieri. The exceptions were isolates BY21311 and BY21312, which belonged to a new species of Pectobacterium polonicum previously found in groundwater. The taxonomy of isolate BY21311 was confirmed using whole genome-based analysis. P. polonicum has only been identified in potato plants on one farm in Baoding region in China. Isolates BY21311 and BY21312 displayed similar physiological and biochemical traits to the type strain DPMP315T. Artificial inoculation assays revealed that isolate BY21311 fulfilled Koch’s postulates for potato blackleg. These findings represent the first time P. polonicum, a water-associated Pectobacterium species may be the cause of blackleg in the field. Interestingly, P. polonicum BY21311 has reduced ability to macerate potato tubers when compared to P. atrosepticum, P. brasiliense, P. versatile, and P. parvum, which is more virulent in tubers than the type strain DPMP315T. The host range of isolate BY21311 was determined by injection method, which can impregnate five plants. Although the genome of isolate BY21311 harbors gene clusters encoding a type III secretion system, it did not elicit a hypersensitive response (HR) in Nicotiana benthamiana or N. tabacum leaves. T3SS effector AvrE and T4SS effector PilN were obtained by predicting isolate BY21311 genome. P. polonicum appears to show significant variations in gene content between two genomes, and gene content varies between isolates BY21311 and DPMP315T, with strain specific-genes involved in many aspects, including lipopolysaccharide biosynthesis, substrate translocation, T4SS and T6SS among others, suggesting that isolates BY21311 and DPMP315T might represent distinct clades within the species.